Project Sourcing for Capstone Course Experience from an Undergraduate Program - GAN, Benjamin (Institutional Knowledge at Singapore Management University, 2015)
Capstone project courses give students experience solving a substantial problem using concepts that span several topic areas in the program of study. Having 280 students graduate every year, requires a substantial effort towards sourcing appropriate projects from the industry and academia that provide hands-on opportunity to apply IT solutions to problems. This paper presents two sourcing models for supporting the sourcing of capstone projects. For each model, the various project origination sources, the distinct attributes, the challenges and lessons learnt are discussed.